Pertanggungjawaban Pidana Terhadap Afiliator Aplikasi Opsi Biner Ilegal Dalam Hukum Pidana Indonesia - Fakhri Rizki Zaenudin; Hana Faridah (Jurnal Hukum Sasana, 2022)
The rapid development of technology in this era of globalization has an impact on the increasing number of people who use electronic media, the use of electronic media has a positive and negative impact, one of the negative impacts of crime can be growing in electronic media for example fraud crimes committed by binary options affiliates from applications Binomo. The purpose of this research is to find out how the criminal liability of illegal binary options affiliates is by committing criminal acts of fraud, and to find out how the validity of electronic evidence is in the criminal procedural law system in Indonesia. The method used in this study is a normative juridical research method, by analyzing primary or secondary legal materials using card system data collection techniques, so that it can be concluded that an illegal binary options affiliate can be threatened with Article 378 Jo Article 55 of the Criminal Code and Article 28 paragraph (1) Law Number 11 of 2008 concerning Information and Electronic Transactions in conjunction with Article 45A paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE), and Electronic evidence in criminal procedural law is considered valid if it meets the provisions in the ITE Law, and guarantees its authenticity by expert witnesses in the field of digital forensics.